Jane eyre - Claybourne, Anna; Harvey, Bob (Usborne Publishing Ltd London, 2013)
Rivetingly retold for today's readers, Charlotte Brontë's classic story remains as exciting as when it was first written. Jane Eyre, a governess at Thornfield Hall soon realizes that Thornfield and its owner, Mr. Rochester, are hiding dark secrets